The changes of laws related to the matura exam in reflection of teaching IT as a secondary grammar school subject Teaching - Biczóné Lengyel, Beáta; Gyöngyösiné Szabó, Judit (Acta Scientiarum Socialium, 2014)
The changes of laws related to the matura exam in reflection of teaching IT as a secondary grammar school subject Teaching IT has changed significantly in the past 30 years. Initially, it was in included in the syllabus of the school subject technology, but as a result of demands it became a separate, independent subject. Its strengthening was blocked by syllabuses prescribing low lesson numbers in school curriculua; then its future became unstable by the new syllabuses in 2013 and the repeated reduction of lesson numbers. However, the responsibility of education is unquestionable. It is important for us to ensure everyone to be able to acquire at least the beginners’ level in digital literacy. For this a strong school IT subject is essential.